How Discount and Bundling Strategies Shape Purchase Decisions Through Brand Image Mediation in Indonesian Retail Context - Mohammad Soni; Ratih Hurriyati; Puspo Dewi Dirgantari (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
In an increasingly competitive business environment, selecting effective marketing strategies is crucial for shaping customer purchase decisions. This study examines how discounts and bundling influence purchase decisions at Kedai Tekun, with brand image as a mediating variable. Using a quantitative approach, surveys were distributed to one hundred customers. Structural Equation Modeling (SEM) via Smart-PLS was employed to evaluate variable relationships. Findings reveal that discounts positively and significantly affect both brand image and purchase decisions, while bundling demonstrates a positive significant impact on purchase decisions. Interestingly, brand image negatively and significantly influences purchase decisions. Mediation analysis confirms discounts have an indirect effect on purchase decisions through brand image. Results suggest discount strategies facilitate consumer purchase decisions, whereas bundling enhances purchase intention. However, brand image requires careful management, as favorable perceptions do not necessarily increase purchase decisions. Business owners should optimize marketing effectiveness by balancing promotional strategies with strengthening brand identity and core values.